2022
DOI: 10.3389/fvets.2022.883607
|View full text |Cite
|
Sign up to set email alerts
|

Getah Virus Infection Rapidly Causes Testicular Damage and Decreases Sperm Quality in Male Mice

Abstract: Getah virus (GETV) is a zoonotic arbovirus that can cause infection in many animals. It can cause pyrexia and reproductive losses in animals. The objective of the study was to explore the effects of GETV on male reproductive ability. Male mice were injected with 100 × TCID50/0.1 ml in a volume of 100-μL GETV in their hindquarter muscle, resulting in decreased semen quality and testicular histopathological changes, and the virus was detected in the testes. At 0.5 dpi (day post-infection), male mice showed decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The results showed that all three infection methods could detect the presence of GETV in all tissues within 24 h of infection, but the order of tissue invasion by different infection methods was different. Li [ 20 ] showed that after intramuscular injection of GETV in mice, the virus appeared in the testicular and caused testicular histopathological changes and decreased semen quality and testosterone levels, which is consistent with our findings. Yang [ 21 ] also found that GETV was detected in multiple organs of getv-infected piglets, indicating that GETV can infect different species with multiple tissue tropisms.…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that all three infection methods could detect the presence of GETV in all tissues within 24 h of infection, but the order of tissue invasion by different infection methods was different. Li [ 20 ] showed that after intramuscular injection of GETV in mice, the virus appeared in the testicular and caused testicular histopathological changes and decreased semen quality and testosterone levels, which is consistent with our findings. Yang [ 21 ] also found that GETV was detected in multiple organs of getv-infected piglets, indicating that GETV can infect different species with multiple tissue tropisms.…”
Section: Discussionsupporting
confidence: 91%
“…Reproductive organs: Since alphaviruses are capable of replicating in the reproductive organs [ 36 , 55 , 56 , 57 ], viral antigen and histology was examined in the reproductive organs after aerosol exposure. The time points alternated between males and females with males being used at 12, 36, and 60 hpi while females were used at 24, 48, and 72 hpi.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, testicular inflammation results in tissue swelling and congestion, leading to an increased tissue weight [ 32 ]. At 7 and 30 dpc, the testicular TSIs in the infected groups were significantly higher than those in the mock-infected group ( p < 0.01; Figure 4a ).…”
Section: Resultsmentioning
confidence: 99%